2010
DOI: 10.1002/acr.20146
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cardiorespiratory aerobic exercise in rheumatoid arthritis: Meta‐analysis of randomized controlled trials

Abstract: Objective. Several lines of evidence have emphasized an improvement in aerobic capacity and muscle strength after physical exercise programs in rheumatoid arthritis (RA) patients. Our objective was to evaluate the efficacy of aerobic exercises in RA on quality of life, function, and clinical and radiologic outcomes by a systematic literature review and a meta-analysis. Methods. A systematic literature search was performed in the Medline, EMBase, and Cochrane databases up to July 2009 and in the abstracts prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
93
0
15

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(120 citation statements)
references
References 41 publications
12
93
0
15
Order By: Relevance
“…We also found, similar to other published studies, that many individuals with RA have very low levels of physical activity (10,11) in spite of the demonstrated safety of exercise and published guidelines recommending physical activity for persons with RA (12). Although studies have examined the impact of exercise interventions on RA outcomes, most have focused on pain or function (13)(14)(15)(16)(17). Two recent systematic reviews found that physical activity did have beneficial effects on fatigue (18,19), but most exercise interventions have been resource intensive, requiring specially trained personnel, highly structured activities, and/or attendance at classes or a specified facility.…”
Section: Introductionsupporting
confidence: 64%
“…We also found, similar to other published studies, that many individuals with RA have very low levels of physical activity (10,11) in spite of the demonstrated safety of exercise and published guidelines recommending physical activity for persons with RA (12). Although studies have examined the impact of exercise interventions on RA outcomes, most have focused on pain or function (13)(14)(15)(16)(17). Two recent systematic reviews found that physical activity did have beneficial effects on fatigue (18,19), but most exercise interventions have been resource intensive, requiring specially trained personnel, highly structured activities, and/or attendance at classes or a specified facility.…”
Section: Introductionsupporting
confidence: 64%
“…[14][15][16][17][18][19][20] However; much less research has been conducted in the broader category of physical activity.…”
mentioning
confidence: 99%
“…Other compelling evidence advocating the importance of aerobic exercises for RA sufferers was that of a systematic review and meta-analysis by Baillet and colleagues. 14 The study found that aerobic exercises improve some of the most important RA patient outcomes: function, quality of life and pain. Moreover, it appears that aerobic exercise decreases radiological damage and pain.…”
Section: Discussionmentioning
confidence: 97%